International Law Policy Against Illegal Migration in Efforts to Eradicate and Prevent Trafficking in Persons - Norbertus Oriwardana; Maidah Purwanti (Journal of Law and Border Protection, 2020)
Thisiarticle describes the problems of crimes against humanity, namely human trafficking and peopleismuggling that occuriin Indonesia. Thereiareithreeicomponents thatiwillibeitheisubject ofithisiarticle.iFirst,ithisiarticleiwillianalyzeitheicausesiofihumanitraffickingiand peopleismuggling in Indonesia. Second,ithisiarticle will examine human traffickingiin Indonesia,iwhich,iasiitiis known,iis a transit country for those who intend to commit transnational crimes. Third, the Indonesian government's efforts to combat human trafficking and people smuggling are viewed from the aspects of international law and immigration crimes. As is well known, from most cases of human trafficking and people smuggling that have occurred, the majority are women and children. Therefore, the crime of smuggling and trafficking in personsiisiaireflectioniofitheiIndonesianigovernmentiwhich does not yet fully have a permanent andibindingilawirelateditoipolicies regulating the movement of people in this case.